1984
DOI: 10.1128/jvi.49.3.828-840.1984
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the envelope gene and long terminal repeat of Friend mink cell focus-inducing virus: implications for the functions of these sequences

Abstract: We sequenced the envelope (env) gene and 3' long terminal repeat of a Friend mink cell focus-inducing virus (F-MCFV). We also sequenced the gp7O coding regions for two cDNA clones of another F-MCFV. The deduced amino acid sequence of the env gene products of both F-MCFVs were compared to the corresponding sequences of other MCFVs and of ecotropic viruses. The env polypeptides of the different viruses showed long stretches of homology in the carboxy-terminal half of gp7O and in p15env ("constant region"). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
87
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 56 publications
4
87
0
Order By: Relevance
“…MCF-like viruses have also been recovered from feline (Neil et aL, 1991) and avian oncogene-murine chimeric systems (Feuer et aL,i993). Other references that provide a useful entry to this field include Adachi et al (1984), Chattopadhyay et aL (1991), Di Fronzo and Holland (1993), Khan et aL (1987), Koch et aL (1984), Levy et al (1985), Makino et al (1990), Oliff et al (1984), Quint et al (1984) and Shields et al (1991).…”
Section: Discussionmentioning
confidence: 99%
“…MCF-like viruses have also been recovered from feline (Neil et aL, 1991) and avian oncogene-murine chimeric systems (Feuer et aL,i993). Other references that provide a useful entry to this field include Adachi et al (1984), Chattopadhyay et aL (1991), Di Fronzo and Holland (1993), Khan et aL (1987), Koch et aL (1984), Levy et al (1985), Makino et al (1990), Oliff et al (1984), Quint et al (1984) and Shields et al (1991).…”
Section: Discussionmentioning
confidence: 99%
“…The primary structure of gp55 closely resembles that of the replication-competent polytropic (dualtropic) MCF MuLV Env protein (1,5,10,21). There are two major modifications in the primary structure of gp55 as compared to that of the MCF MuLV Env protein.…”
mentioning
confidence: 94%
“…Previously, we reported that genetically engineered F-SFFV encoding the mutant gp55 which has an ecotropic F-MuLV (clone K-1) gp70 amino-terminal region instead of the MCF MuLV gp70 sequences was nonpathogenic (19). Since the ecotropic F-MuLV gp70 amino-terminal region has, at most, about 30% sequence identity to the MCF MuLV gp70 amino-terminal region with several gaps introduced (10), differences other than those causing the inability to bind to the MCF MuLV receptor protein in the primary structure of this mutant The indicated number (from 10i to 101) of BS-resistant Ba/F3 or BER28C cells expressing either wild-type (WT) gp55 or XE gp55 was inoculated in 24 wells of a 24-well multiwell plate (0.4 mllwell) using medium without Epo or IL-3. Ten days after inoculating the cells, the number of wells with growing cells was scored by microscopic observation.…”
mentioning
confidence: 99%
“…8) and is very similar to the sequences obtained for other murine retroviruses. It contains the transcriptional regulatory sequences and short terminal repeats that are characteristic of retroviral LTRs, but it lacks the 65to 75-base-pair repeat in the U3 region which occurs in Moloney MuLV, Moloney murine sarcoma virus, and F-MuLV (22). A comparison of the homology between the R-SFFV LTR and related MuLV LTRs is presented in Fig.…”
mentioning
confidence: 99%
“…There is greater than 95% homology between R-SFFV and the three viruses presented, F-SFFV, Friend mink cell focus-inducing leukemia virus (F-MCF), and F-MuLV. Because the tissue tropism of murine retroviruses has recently been associated (6,22) with the U3 domain of LTRs, which also are known to contain enhancers of transcription, a search was made for homology to a putative enhancer "core sequence" (23,24) in the U3 domain of the R-SFFV LTR. At the same relative position in the R-SFFV U3 (Fig.…”
mentioning
confidence: 99%